Urban adaptation to mega-drought: Anticipatory water modeling, policy, and planning for the urban Southwest. (November 2016) - Gober, Patricia; Sampson, David A.; Quay, Ray; White, Dave D.; Chow, Winston T.L.
Highlights: 'Medieval' drought conditions are simulated for water resources in metro Phoenix. Anticipatory models enable long-term policy analysis for climate change. Mega-drought results in unsustainable groundwater use between 2000 and 2060. Aggressive drought management policies can produce sustainable yield. The time to manage droughts is before they occur. Abstract: This paper uses 'Medieval' drought conditions from the 12th Century to simulate the implications of severe and persistent drought for the future of water resource management in metropolitan Phoenix, one of the largest and fastest growing urban areas in the southwestern USA. WaterSim 5, an anticipatory water policy and planning model, was used to explore groundwater sustainability outcomes for mega-drought conditions across a range of policies, including population growth management, water conservation, water banking, direct reuse of RO reclaimed water, and water augmentation. Results revealed that business-as-usual population growth, per capita use trends, and management strategies are not sustainable over the long term, even without mega-drought conditions as years of available groundwater supply decline over the simulation period from 2000 to 2060. Adding mega-drought increases the decline in aquifer level and increases the variability in flows and uncertainty about future groundwater supplies. Simulations that combine drought management policies return the region to levels that are more sustainable. Results demonstrate the value of long-term planning and policy analysis for anticipating and adapting to environmental and societal change. Similar anticipatory exercises can be used to assess different suites of drought management policies in other cities facing uncertainty about future conditions.